Multi-Omics Analysis Provides Insights into a Mosaic-Leaf Phenotype of Astaxanthin-Producing Tobacco - Jialin Wang; Zaifeng Du; Xiaoyang Lin; Peng Li; Shihao Sun; Changqing Yang; Yong Chen; Zhongfeng Zhang; Xue Yin; Ning Fang (Plants)
In metabolically engineered plants, the target products are usually uniformly distributed in the whole plant or specific tissues. When engineering tobacco to produce astaxanthin, a ketocarotenoid with strong antioxidant activity and multiple bioactivities, a scattered distribution of astaxanthin-producing regions was observed in a small portion of astaxanthin-producing tobacco plants, which caused mosaic-like red and green spots on the leaves (ASTA-mosaic). A physiological assay showed that the non-astaxanthin green region (Mosaic_G) had relatively higher chlorophyll content and better chloroplast structure than the astaxanthin-producing red region (Mosaic_R). Then, metabolomics, proteomics, and small RNA transcriptomics were employed to analyze the uneven distribution of astaxanthin-producing regions in tobacco leaves. The results of metabolomics and proteomics revealed a decrease in carotenoid metabolism, chlorophyll biosynthesis, and chlorophyll degradation in the Mosaic_G region. Pheophorbide a, an intermediate of chlorophyll degradation, was found to be significantly reduced in the Mosaic_G region, which was accompanied by the attenuation of chlorophyllase and pheophytinase, which catalyze the formation of pheophorbide a in chlorophyll degradation. Reductions in photosynthetic antenna proteins and photosystem-associated proteins were observed in the Mosaic_R region, consistent with the better chloroplast structure of the Mosaic_G region. Small RNA transcriptomics showed that several small RNAs could target chlorophyll-degradative genes, but they were more effective in targeting the astaxanthin biosynthetic genes. This finding was supported by the fact that the Mosaic_G region can remain green up to the senescence of tobacco leaves. This work provides insights into the mechanism of the uneven distribution of astaxanthin-producing regions in tobacco leaves and may contribute to the specialized utilization of tobacco plants for metabolic engineering.